Policy analysis in Colombia - Sanabria-Pulido, Pablo; Rubaii, Nadia (International library of policy analysis., 2020)
A systematic overview of policy analysis in Colombia and an instructive view of how it might help studies elsewhere. Leading academics assess central and local policy in fields including health, education and the military, and explore their role in Colombia's economic development, resolution of internal conflict, and other successes.